Differences of the weighted differentiation composition operators from mixed-norm spaces to weighted-type spaces - Chen, Cui; Zhou, Ze-Hua (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We characterize the boundedness and compactness of the differences of weighted differentiation composition operators D^n_φ_1, u_1 - D^n_φ_2, u_2, where n N_0, u_1, u_2 H(D), and φ_1, φ_2 S(D), from mixed-norm spaces H(p, q, φ), where 0 < p, q < ∞ and φ is normal, to weighted-type spaces H^∞_v.